Improving the quality of public health services in lower income areas in Cairo, Egypt: a comparative study between the accredited and non-accredited primary health care clinics in Cairo - Abdel Latif, Amira Moukhtar (AUC Knowledge Fountain, 2013)
This thesis deals with the quality of public health services in the primary health care clinics in lower income areas in Cairo. There are multiple factors affecting such quality, including the motivation of the workforce, the infrastructure and equipment of the facility, and the modes of finance and management. The research examines whether the accreditation of health clinics by the Egyptian Ministry of Health and Population affects these factors and hence improves the quality of the service provided. To do this, the research is based on a comparative study between accredited and non-accredited health care facilities; where accreditation is granted based on patients’ rights, patients’ care, environmental and clinical safety, information management, clinical and non clinical services, and management of the facility, quality improvement program, and integration of care. Although the accreditation period has expired for all accredited facilities in Cairo, some improvements to the quality of health care services were introduced as a result of the accreditation. Forty four interviews were conducted with public health workers and health service visitors (patients) in two accredited clinics and two non- accredited. The interviews were transcribed and data was analyzed using qualitative method of analysis. The results have shown that the accredited clinics are more organized, regularly inspected, and hence patients are more satisfied with the quality of service. However, it was noted that there are common impediments to improvement of health services in all public health clinics, like; poor equipments, old outdated devices, lack of utilities, and insufficient medicine supply; which act as de-motivating factors to most of the health workers. The thesis comes to the conclusion that these common factors point out to the need for wider reforms in the health service sector beyond introducing the accreditation system of public health clinics. These reforms should focus on a considerably more investment in the health service sector to modernize the service as well as improving the incentive system for health workers, improving the processes of purchase and maintenance of equipment, revising the essential drug list, and focusing on patients’ education.